Basin Classification Based on Quantitative Geological Risk Factors - Irham, Syamsul; Sulaksana, Nana; Sudrajat, Adjat; Burhanidunnur, Muhammad (Bulletin of Scientific Contribution, 2018)
Abstract. Indonesia's oil and gas reserves are small and certainly will run out quickly if production is not followed by additional efforts. Exploration activities are not only one effort but also the first step of all efforts to increase reserves through the discovery of oil and gas resources. Efforts are needed to attract exploration investment interests, including access into available data, presentation of results from exploration activities and geological risk. The present research aims to study the characteristics of the geological risk in several basins based on the quantitative geological factors. In conducting the quantitative analysis, there are some factors of petroleum system that have to be recognized inter alia, source rock, reservoir, seal, trap, migration, fault and fold. For this purpose, six basins were selected representing frontier, semi mature and mature basins. Three basins were taken from the western part of Indonesia, and three others from the eastern part.